ANALISIS PUTUSAN VERSTEK KUMULASI ISBAT NIKAH DAN CERAI GUGAT (Studi Perkara Nomor: 135/Pdt.G/2022/PA.Pbg) - Nurhidayattulloh, M.; Huda, Misbahul (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2024)
One of the problems in marriage law is divorce which is preceded by the practice of unregistered marriage. The decision with number: 135/Pdt.G/2022/Pa.Pbg is interesting to examine because it is the first verdict on the cumulative isbat marriage and divorce lawsuit at the Purbalingga Religious Court. The focus of the problem in this research is how the judge’s legal considerations are in the case of cumulating marriage isbat and divorce lawsuits in Decision Number: 135/Pdt.G/2022/Pa.Pbg and what the normative juridical review is. The research, including field research, is descriptive analysis using a normative juridical approach. Data collection techniques were carried out using observation, documentation and interviews. The results of the research showed that the panel of judges declared the marriage between the plaintiff and the defendant valid because they had fulfilled the requirements and terms of marriage and imposed the defendant’s talaq ba’in sughra on the plaintiff because the defendant had left the plaintiff within a period of 4 years and 9 months. The basic legal considerations used by the judge in deciding case Number: 135/pdt.g/2022/Pa.Pbg are in accordance with statutory regulations and Islamic law